Psychological Problems of Pediatric Patients with Thalassemia: A Narrative Literature Review - Fenny Pranandita (HM Publisher, 2021)
Thalassemia is a chronic condition with a variety of clinical and psychological complications. The onset of symptoms, the rigors of therapy, and frequent absences from school significantly strain the emotional and interpersonal resources of children and their families. This review aimed to describe psychological problems in patients with thalassemia. Adolescents with thalassemia major often experience pain and should be given restrictions in terms of activity. This restriction must be done to maintain the condition of adolescents with thalassemia major who are quickly tired. Psychosocial is part of the quality of life of adolescents with thalassemia major, so when the psychosocial of adolescents is disturbed, it will affect their quality of life. Social isolation, decreased self-esteem, low academic achievement, and a terrible stigma will lead to the psychological burden of thalassemia adolescents. In conclusion, psychosocial problems arise in adolescents with thalassemia caused by body image disturbances experienced so that they feel distrustful and limit their association with their peers, restrictions on activities provided by health workers and parents, and low academic achievement that makes thalassemic adolescents experience psychological and psychological problems decreased quality of life.